Деякі собливості багатопрохідного плоского торцевого шліфування - Пижов, Іван Миколайович; Клименко, В. Г. (НТУ "ХПІ", 2014)
Виконано дослідження, що дали можливість виявити деякі особливості формування макро- і мікропрофілю оброблюваної поверхні при багатопрохідному плоскому торцевому шліфуванні з нахилом осі шпинделя. Встановлено роль у цьому процесі таких факторів, як кут нахилу осі шпинделя, діаметр круга і поперечна подача, і запропонована емпірична залежність, що зв'язує з ними висоту залишкових гребінців. Це дозволяє розширити уявлення про технологічні можливості процесу плоского торцевого шліфування.

The studies that made it possible to identify some features of the formation of work surface macro-and microprofile under multiple-pass face flat grinding with inclination of the center line of spindle are fulfilled. A feature of this grinding process is the formation of residual ridges on the surface of the workpiece. This is different from through-feed grinding processing. Theoretically, depending on the magnitude of the cross-feed, residual ridges may be defined as the surface roughness and form deviation. In the latter case there is a such variant of form deviations as concavity. It is found that the value of a cross feed should be prescribed as the part of width of the contact between the working surface of the face wheel and workpiece which is formed in one pass with the concrete depth of grinding. Computer modeling of the contact area of the working surface of the grinding wheel with the workpiece in the COMPASS software environment has allowed to reveal the character of influence of processing conditions on the magnitude of residual ridges. Role has been installed for such factors of this process as the inclination angle of the center line of spindle, the diameter of the wheel and cross feed, and it has been proposed an empirical dependence linking the height of residual ridges with them. It is shown that the height of the residual ridges associated with a diameter of the wheel and cross feed by the degree dependences. The dependence on the inclination of the center line of spindle is linear. This allows expand the understanding of the technological capabilities of the flat face grinding process.
Keywords: обробка матеріалу; машинобудування; шліфування; кут нахилу